Innovation and evaluation. Proposals for improving cross-project training university students in Education - Antonio Romero Muñoz; Inmaculada González Falcón (Revista Interuniversitaria de Formación del Profesorado, 2010)
This article reflects the results of the evaluation in the educational innovation project called "City of Rainbows", that has been developed at the University of Huelva since the academic year 2002/03.The experience, aims, tools and the process of evaluation followed are briefly described in it, focusing especially on evaluation an proposals for improvement which the various participants (faculty lecturer, students of Education, and actual teachers) make on the impact of this innovation project to train the students of the Faculty of Education